Penerapan Metode Perbandingan Eksponensial (MPE) Dalam Sistem Pendukung Keputusan Penilaian Kinerja Satpol PP - Vebi Hardiansyah; Jusuf Wahyudi; Indra Kanedi; Sastya Hendri Wibowo (Jurnal Media Infotama, 2026)
Performance Evaluation of Satpol PP is an important aspect in improving work effectiveness and professionalism. However, the subjective and unstructured appraisal process often leads to unfairness and inaccuracy in decision making. To overcome this problem, this study implements the Exponential Weighted Average (EWA) method in a Decision Support System (DSS) to provide a more objective, systematic, and measurable performance evaluation. EWA is used to compare various performance criteria exponentially, resulting in more accurate assessment weights based on their level of importance. The criteria used include discipline, responsibility, teamwork, initiative, and leadership. With the aim of assisting the government of Bengkulu City in assessing the performance of Satpol PP, it can be concluded that this will simplify the data input process and the presentation of evaluation results. The results of the implementation show that the system built is capable of providing consistent performance assessment recommendations that are acceptable to Satpol PP management. Thus, the implementation of ECM in DSS has proven to be effective in supporting a more fair and transparent performance assessment decision-making process.